2014
DOI: 10.1016/j.eatbeh.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The association of “food addiction” with disordered eating and body mass index

Abstract: Introduction The contribution of an addictive process to elevated body mass index (BMI) and disordered eating is an area of growing interest. Yet, little is known about how “food addiction” may be related to disordered eating and obesity. The ability of addictive-like eating to account for eating pathology not captured by traditional eating disorders is unknown. No prior research has examined the association of “food addiction” with bulimia nervosa (BN). Finally, little is understood about the association of “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
207
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(245 citation statements)
references
References 49 publications
30
207
1
7
Order By: Relevance
“…Our finding that the prevalence of food addiction did not differ by BMI categories is also consistent with a prior study conducted by Gearhardt, et al 11 However, several other studies 7,12,13 observed a substantially higher prevalence of food addiction among obese individuals. This could be due to an addictive-type response to highly palatable foods resulting in obesity.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding that the prevalence of food addiction did not differ by BMI categories is also consistent with a prior study conducted by Gearhardt, et al 11 However, several other studies 7,12,13 observed a substantially higher prevalence of food addiction among obese individuals. This could be due to an addictive-type response to highly palatable foods resulting in obesity.…”
Section: Discussionsupporting
confidence: 82%
“…Three studies found high values of comorbidity between BED and FOA as defined by the YFAS as follows: 72% (141), 56.8% (133), and 41.5% (134). The considerable overlap between FOA and BED and also other eating disorders such as anorexia and bulimia nervosa (147)(148)(149) raises the following important question: is FOA a unique nosological entity?…”
Section: Loss Of Control Over Hedonic Food Intake: Foamentioning
confidence: 94%
“…Prevalence of FA diagnosis was meta-analyzed by sex with a higher mean prevalence of FA in six samples of females exclusively of 12.2% [35,40,45,47,51,57] compared to 6.4% in four samples of males [45,47,51,57]. When meta-analyzed by BMI category, the mean prevalence of FA was considerably greater at 24.9% in fourteen studies investigating overweight/obese individuals (Figure 2b) [27,[34][35][36][37][38][39][44][45][46][47]49,51,56,57] compared to 11.1% in six studies of healthy weight individuals (Figure 2c) [26,28,32,43,51,53]. The mean FA prevalence was lower in nine samples of adults younger than 35 years of age at 17.0% [26,32,34,36,40,43,47,53,57] compared to 22.2% in eleven samples of adults aged over 35 years [27,35,…”
Section: Meule 2014mentioning
confidence: 99%